13P-MR spectroscopy for the evaluation of energy metabolism in intact residual myocardium after acute myocardial infarction in humans - Beer, M; Buchner, S; Sandstede, J; Viehrig, M; Lipke, C; Krug, A; Köstler, H; Pabst, T; Kenn, W; Landschütz, W; Von Kienlin, M; Harre, K; et al. (2001)
Objective: Experimental studies have demonstrated that acute myocardial infarction (MI) alters energy metabolism even in non-infarcted adjacent tissue. In patients with subacute MI, the influence of the regional ischemic insult on energy metabolism of intact septal myocardium was analyzed using 31P-Magnetic resonance spectroscopy (MRS). Patients and Methods: In eight patients with wall motion abnormalities in the anterior wall 31P-spectra were obtained from non-infarcted adjacent septal myocardium, as well as infarcted anterior myocardium (voxel size 25 ccm each) 29 ± 8 days after MI using a 3D-CSI technique. Additionally, cardiac function was analyzed using breath-hold cine MRI. MRI was repeated 6 months after revascularization to assess viability of infarcted segments. Eight age-matched healthy volunteers served as control group. Results: According to follow-up MRI 4/8 patients showed regional wall motion recovery. Here, PCr/ATP-ratios were not significantly reduced in intact septal myocardium as well as infarcted anterior myocardium compared to healthy volunteers (1.28 ± 0.10 and 1.14 ± 0.09 vs. 1.45 ± 0.29). No recovery of regional function was detected in 4/8 patients with - therefore - nonviable anterior myocardium. PCr/ATP-ratios were significantly reduced in intact and infarcted myocardium compared with healthy volunteers as well as to patients with wall motion recovery (0.77 ±0.17 and 0.49 ±0.23; P<0.05). Discussion: These preliminary results indicate that energy metabolism is reduced in patients with persisting wall motion abnormalities after myocardial infarction and revascularization in ischemically injured as well as in adjacent non-injured myocardium. © 2001 Elsevier Science B.V. All rights reserved.